Characteristics of the Metacognitive Skill Evaluation Instrument in Merdeka Curriculum Biology Learning - Pratami, Dita Aulia; Indriyanti, Dyah Rini; Parmin, Parmin; Ellianawati, Ellianawati; Widiyatmoko, Arif (Universitas Negeri Semarang, 2025)
Metacognitive will encourage students manage cognitive activities which be con trolled. This research aims to develop instruments that can measure students’ metacognition as an implementation of the Merdeka Curriculum. This research according to the ADDIE model. The research was conducted on students who had studied Environmental Change material in class X, with a small-scale trial on 10 students, and a large-scale trial on 50 students. Qualitative data analysis is in the form of descriptive validator comments. Quantitative data analysis includes validity, reliability, differentiated, question difficulty, and product effectiveness tests. Based on the development study, this product consists of 4 indicators, that is knowledge, regulation, awareness, and responsiveness. The instrument can ef fectively measure students’ metacognition, with the proportion of achievement of metacognitive integrated questions is 68%, and metacognitive questionnaires is 72%. The percentage of metacognitive integrated questions is 73.362%, with a KMO value is 0.875, and the fit category as a measurement instrument is 48%. The percentage of metacognitive questionnaire measurability is 82.123, with a KMO value is 0.578, and a fit category as a measurement instrument is 20%.